Infection Biology of Bipolaris oryzae in Rice and Defence Responses in Compatible and Less Compatible Interactions - Tran Thi Thu Thuy; Mette Lübeck; Viggo Smedegaard-Petersen; Eigil de Neergaard; Hans J. L. Jørgensen (Agronomy, 2023)
The infection biology of Bipolaris oryzae and the defence responses of its host rice were studied using the rice cv. MTL 189 inoculated with two isolates of B5 (highly compatible with MTL 189) and K2 (less compatible). In the former interaction, the hyphal progress was accompanied by tissue degradation and extensive sporulation after 8 days, whereas in the latter interaction, only very limited tissue degradation and sporulation was observed. Quantitative microscopy of the infection showed that the percentages of conidia and appressoria causing penetration and fluorescent epidermal cells (FEC) were lower for isolate K2 than for isolate B5 at 12 and 24 hours after inoculation (hai). Fluorescent papillae (FP) were only seen in the less compatible interaction and the percentage of conidia causing single FEC was highest in the less compatible interaction at 12 hai, but not at 24 hai. Qualitative examination of other defence responses showed that H2O2 started to accumulate at 4 hai in the less compatible interaction, whereas it appeared in the compatible interaction only at 12 hai. The level of H2O2 was generally higher in the less compatible than in the compatible interaction. Cross sections of leaves showed that H2O2 accumulated in the outer walls of epidermal cells. Likewise, accumulation of callose and polyphenolic substances was most pronounced in the less compatible interaction and occurred at the same places as H2O2. To our knowledge, this is the first report implicating H2O2 as an early defence response against the hemibiotrophic pathogen B. oryzae during early infection stages in rice. Understanding defence reactions may aid in resistance breeding.